2010
DOI: 10.1016/j.jjcc.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep apnea syndrome and sleep blood pressure in patients without hypertension

Abstract: The results of this study suggested that SAS affected nocturnal BP elevation even in SAS patients without HTN. The diurnal BP showed no difference in the severity of SAS; however, the severe-SAS group revealed significant nocturnal BP elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
(32 reference statements)
1
15
0
2
Order By: Relevance
“…Also, there are a few studies employing ambulatory 24-hour BP monitoring (ABPM) instead of single time-point BP measurement, but these typically included a number of subjects two orders lower than in the current study. In a group of 47 consecutive patients, Sekizuka et al 31 report a significantly higher morning BP measured minutes after awakening and a higher nocturnal BP in se-OSA than in non se-OSA groups. Similarly, Cho et al 32 note that both morning SBP and DBP positively correlated with AHI, with a trend toward slightly higher correlation quotient for DBP, in a group of 58 patients with naïve hypertension.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Also, there are a few studies employing ambulatory 24-hour BP monitoring (ABPM) instead of single time-point BP measurement, but these typically included a number of subjects two orders lower than in the current study. In a group of 47 consecutive patients, Sekizuka et al 31 report a significantly higher morning BP measured minutes after awakening and a higher nocturnal BP in se-OSA than in non se-OSA groups. Similarly, Cho et al 32 note that both morning SBP and DBP positively correlated with AHI, with a trend toward slightly higher correlation quotient for DBP, in a group of 58 patients with naïve hypertension.…”
mentioning
confidence: 95%
“…Our findings on the relationship between BP and AHI may be weakened by the occurrence of masked hypertension in patients with OSA (ie, some patients with normal clinical BP actually may have had an elevated ABPM, which would otherwise strengthen this relationship). 34 However, these three studies did not correct for the possible confounding effect of sex, age, or BMI on the associations, although Sekizuka et al 31 mentioned a possible interplay between high BP, OSA, and obesity. Yet, future studies should adopt this approach (ie, combining PSG and ABPM, when examining larger groups of normotensive OSA patients) to deepen the understanding of the relationship between breathing disturbances during sleep and BP circadian variability.…”
mentioning
confidence: 99%
“…The result of this study is similar to that of our previous study. 4 It has been reported that nocturnal hypertension contributes to the occurrence of cardiovascular disease and target organ damage. 1,2 Many investigators have reported that the risk of sudden death, heart failure or acute myocardial infarction increases during sleep in obstructive SAS patients.…”
Section: Influential Factors In Circadian Bp Changesmentioning
confidence: 99%
“…Treatment of SAS prevents sleep BP elevation. 4 Along with this treatment, improvement of lifestyle and eating habits is required to lower BP and improve abnormal lipid metabolism and glucose tolerance. Both of these factors probably prevent nocturnal hypertension, a risk factor for the onset of cardiovascular events.…”
Section: Influential Factors In Circadian Bp Changesmentioning
confidence: 99%
See 1 more Smart Citation